2020
DOI: 10.1177/0020872820959365
|View full text |Cite
|
Sign up to set email alerts
|

The more you know, the less you fear: Reflexive social work practices in times of COVID-19

Abstract: In this article, we present the results of a strategy to disseminate best social work practices during periods of social lockdown in Spain, in a climate characterised by post-truth, misinformation and fake news. Social work is challenged with the task of delivering reliable and quality information aimed at building a better society. At the time of writing, Spain was one of the countries most affected by COVID-19, with one of the highest numbers of deaths per million inhabitants in the world. With the populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 6 publications
2
17
0
Order By: Relevance
“…The situation was aggravated by numerous fake information and conspiracy theories, which flooded social networks. It is no secret that even some opinion leaders, including heads of state, often disseminated false information, misleading citizens and forcing scientists and doctors to refute it, which is consistent with the findings of López Peláez et al (2020) and Yum (2020). Due to the lack of information about the virus and experience in working in a pandemic and lockdown, social workers, especially in the first months, found themselves in an information vacuum, and national governments did not always have time to issue and promptly update instructions that meet the requirements of work in a rapidly changing environment, as Dauti et al (2020) and Redondo-Sama et al (2020) also concluded.…”
Section: Risk Of Infectionsupporting
confidence: 55%
See 2 more Smart Citations
“…The situation was aggravated by numerous fake information and conspiracy theories, which flooded social networks. It is no secret that even some opinion leaders, including heads of state, often disseminated false information, misleading citizens and forcing scientists and doctors to refute it, which is consistent with the findings of López Peláez et al (2020) and Yum (2020). Due to the lack of information about the virus and experience in working in a pandemic and lockdown, social workers, especially in the first months, found themselves in an information vacuum, and national governments did not always have time to issue and promptly update instructions that meet the requirements of work in a rapidly changing environment, as Dauti et al (2020) and Redondo-Sama et al (2020) also concluded.…”
Section: Risk Of Infectionsupporting
confidence: 55%
“…Social workers faced a new pandemic-related challenge: the huge number of rumors and conflicting information made the population feel insecure, fearful, and sad. In some groups, this enhanced the drive for control, while in others, it led to an underestimation of the risk of infection, suggesting that alternative explanations for the virus and its lethality are correct (López Peláez et al, 2020). In this regard, social networks played a crucial role, through which opinion leaders and ordinary citizens spread both truthful and fake information about the coronavirus and its origin, including various conspiracy theories (Yum, 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Dominelli (2020) in a UK context and Gergerich et al (2020) in a US context note that many workers are working remotely during the pandemic and that this is impacting service delivery. Researchers across a range of countries including the UK ( Cook and Zschomler, 2020 ; Dominelli, 2020 ), Canada ( Archer-Kuhn et al , 2020 ), Malaysia ( Azman et al , 2020 ), Netherlands ( De Jonge et al , 2020 ), Vietnam ( Dinh and Nguyen, 2020 ), Spain ( López Peláez et al, 2020 ), Poland ( Necel and Zaręba, 2020 ), Greece ( Papouli et al , 2020 ), Lebanon ( Badran, 2020 ), Italy ( Fargion et al , 2020 ) and China ( Yuan et al , 2020 ) note also that workers are using remote technologies to work with clients.…”
Section: Safeguarding Vulnerable Community Membersmentioning
confidence: 99%
“…Indeed, social workers are reporting psychological difficulties among UAMs in accepting the restrictive pandemic measures. The reported "Libyan Syndrome" suggests that existing mistrust in immigration and welfare services is now particularly pronounced as UAMs struggle to reconcile previous traumatic experiences of a curtailment of freedom and autonomy within this new pandemic context (López Peláez et al 2020). Similar previous traumas were reported by social workers in Greece, where UAMs deny the reality of the pandemic.…”
Section: Discussionmentioning
confidence: 77%